2019
DOI: 10.1073/pnas.1906653116
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation of targeted AAVP vectors for systemic transgene delivery against cancer

Abstract: Bacteriophage (phage) have attractive advantages as delivery systems compared with mammalian viruses, but have been considered poor vectors because they lack evolved strategies to confront and overcome mammalian cell barriers to infective agents. We reasoned that improved efficacy of delivery might be achieved through structural modification of the viral capsid to avoid pre- and postinternalization barriers to mammalian cell transduction. We generated multifunctional hybrid adeno-associated virus/phage (AAVP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 51 publications
2
52
0
Order By: Relevance
“…The vector is a hybrid [ 5 , 6 ] in which the phage capsid incorporates hybrid genomes of single-stranded human adeno-associated virus (AAV-2) DNA and the fd phage single-stranded genome. Moreover, to allow entry into cancer cells, we used the Nobel Prize-awarded phage display technology to engineer a phage capsid displaying the double-cyclic RGD4C ligand that binds the α v β 3 integrin cell surface receptor overexpressed on tumor cells and tumor vasculature in most cancers but is barely detectable in healthy tissues [ 7 , 8 , 9 ]. Upon cell entry of the hybrid RGD4C/AAV-phage (RGD4C/AAVP), the AAV transgene cassette is released, resulting in gene expression in tumors from a cytomegalovirus, CMV , promoter [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vector is a hybrid [ 5 , 6 ] in which the phage capsid incorporates hybrid genomes of single-stranded human adeno-associated virus (AAV-2) DNA and the fd phage single-stranded genome. Moreover, to allow entry into cancer cells, we used the Nobel Prize-awarded phage display technology to engineer a phage capsid displaying the double-cyclic RGD4C ligand that binds the α v β 3 integrin cell surface receptor overexpressed on tumor cells and tumor vasculature in most cancers but is barely detectable in healthy tissues [ 7 , 8 , 9 ]. Upon cell entry of the hybrid RGD4C/AAV-phage (RGD4C/AAVP), the AAV transgene cassette is released, resulting in gene expression in tumors from a cytomegalovirus, CMV , promoter [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon cell entry of the hybrid RGD4C/AAV-phage (RGD4C/AAVP), the AAV transgene cassette is released, resulting in gene expression in tumors from a cytomegalovirus, CMV , promoter [ 5 , 6 ]. We have reported that this vector targets numerous cancer models in vivo upon intravenous delivery [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. A study in pet dogs with spontaneous cancers proved the safety of repeated vector dosing, resulting in complete tumor eradication in a few dogs with aggressive cancers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study, a bacteriophage displaying a CPP was used as a shuttle to deliver an adeno-associated virus (AAV) gene. AAV, cloned within the single-stranded genome of the bacteriophage [ 114 , 115 , 116 , 117 ], contained a mammalian transgene cassette encoding the cytomegalovirus (CMV) promoter-driven transgene, such as GFP and luciferase, as well as a polyA region that was flanked by inverted terminal repeats (ITRs) from AAV2 genome [ 116 , 117 ]. In the reported studies, Arg-Gly-Asp (RGD-4C) peptide targeting αv integrin receptors on vascular endothelial cells was displayed at N-terminus of phage PIII protein to facilitate AAV-phage cell entry.…”
Section: Cell-based In Vitro Assaysmentioning
confidence: 99%
“…The hybrid adeno-associated virus (AAV)/phage (AAVP) has been successfully used in several in vivo models to target solid tumors with greater specificity, facilitating positron emission tomography (PET) imaging and suppressing tumor growth by disrupting tumor angiogenesis. In PNAS, Suwan et al (2) increase the versatility of AAVP by designing 2 phages capable of avoiding nonspecific adsorption and escaping endosomal-mediated degradation, significantly improving the transduction outcome. This work not only will have important implications for phage-mediated cancer gene therapy but may also facilitate similar optimizations in other gene transfer vectors.…”
mentioning
confidence: 99%